2020
DOI: 10.1111/1759-7714.13705
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognostic implications of ASCL1 expression in surgically resected small cell lung cancer

Abstract: Background: Small cell lung cancer (SCLC) is one of the most aggressive lung cancers. Treatment of SCLC has remained unchanged during the past decades. Preclinical studies have revealed ASCL1 as a transcription regulator in the neuroendocrine (NE) differentiation and carcinogenesis of SCLC. However, there are few studies on correlation of ASCL1 expression and clinicopathological factors in resected SCLCs. Here, we aimed to analyze the ASCL1 expression of SCLC and investigate its associations with clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Since RB1 status was not detected in our study, we were curious to scrutiny this apparently discrepancy of their study and found that nearly half of RB1 expression did not co-express YAP1 both in cell lines and tumors, which may explain the reverse trend towards survival of YAP1 expression. Recently, a few studies has been investigated the distribution pattern and prognostic value of ASCL1 expression in SCLC tumors at the protein level by IHC, yielding to a broader range of 42.5-80% for ASCL1 expression and a significant tendency of prolonged OS for ASCL1 negative group (22)(23)(24). Herein, the destructive effect of ASCL1 subtype on OS and DFS were also obtained both in mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since RB1 status was not detected in our study, we were curious to scrutiny this apparently discrepancy of their study and found that nearly half of RB1 expression did not co-express YAP1 both in cell lines and tumors, which may explain the reverse trend towards survival of YAP1 expression. Recently, a few studies has been investigated the distribution pattern and prognostic value of ASCL1 expression in SCLC tumors at the protein level by IHC, yielding to a broader range of 42.5-80% for ASCL1 expression and a significant tendency of prolonged OS for ASCL1 negative group (22)(23)(24). Herein, the destructive effect of ASCL1 subtype on OS and DFS were also obtained both in mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a few studies has been investigated the distribution pattern and prognostic value of ASCL1 expression in SCLC tumors at the protein level by IHC, yielding to a broader range of 42.5-80% for ASCL1 expression and a significant tendency of prolonged OS for ASCL1 negative group ( 22 24 ). Herein, the destructive effect of ASCL1 subtype on OS and DFS were also obtained both in mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work already showed ASCL1 was a NE related marker. 15 As an inhibitory ligand of Notching pathway, DLL3 also plays an essential role in NE transformation and maintenance. We analyzed the relationship between DLL3 expression and several conventional NE markers, such as SYN, CgA, CD56, and TTF1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…ASCL1 (ab74065, Abcam) and DLL3 (E3J5R, Cell Signal Technology) staining was examined on SCLC tissue microarrays. The SCLC tissue microarrays of the 247 cases were constructed as described previously 15 . All the staining was carried out on the fully automatic Roche IHC instruments (Roche Diagnosis) according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation